A prospective randomized, controlled trial of eculizumab to prevent ischemia‐reperfusion injury in pediatric kidney transplantation. (29th January 2018) - Kaabak, Michael; Babenko, Nadeen; Shapiro, Ron; Zokoyev, Allan; Dymova, Olga; Kim, Edward
Abstract: Ischemia‐reperfusion injury has multiple effects on a transplanted allograft, including delayed or impaired graft function, compromised long‐term survival, and an association with an increased incidence of rejection. Eculizumab, a monoclonal antibody blocking terminal complement activation, has been postulated to be an effective agent in the prevention or amelioration of IRI. We performed a single‐center prospective, randomized controlled trial involving 57 pediatric kidney transplant recipients between 2012 and 2016. The immunosuppressive protocol included two doses of alemtuzumab; half of the patients were randomized to receive a single dose of eculizumab prior to transplantation. Maintenance immunosuppression was based on a combination of low‐dose tacrolimus and mycophenolate, without steroids. Eculizumab‐treated patients had a significantly better early graft function, less arteriolar hyalinosis and chronic glomerulopathy on a protocol biopsies taken on day 30, 1 year, and 3 years after transplantation. In the eculizumab group, four non‐vaccinated children lost their grafts during the course of a flu‐like infection. Eculizumab is associated with better early graft function and improved graft morphology; however, there was an unacceptably high number of early graft losses among the eculizumab‐treated children. While a promising strategy, the best approach to complement inhibition remains to be established.